EFFECT OF ORGANIC MINERAL SUPPLEMENTATION ON BLOOD BIOCHEMISTRY, PLASMA ANTIOXIDANT ENZYME ACTIVITIES AND THEIR CORRELATION TO SPERM FUNCTIONAL CHARACTERISTICS IN OSMANABADI BUCKS - ARANGASAMY, A; J NAIDU, SHARANYA; HEMALATHA, K; SHARMA, RENU; SELVARAJU, S; KRISHNAIAH, M VENKATA; RANI, G P; BINSILA, B K; RAVINDRA, J P; RAGHAVENDRA, B (The Indian Journal of Animal Reproduction, 2022)
This study was carried out to investigate the effect of organic copper (Cu) and zinc (Zn) supplementation onblood biochemical parameters and antioxidant enzyme properties in growing Osmanabadi goats at the onset ofpuberty and semen quality. Forty bucks (five months) were allocated randomly into ten groups, all were fed with basalroughage and a concentrate mixture (50 : 50) supplemented (for a period of 8 months) either with different doses oforganic Zn : 20 mg (T1), 40 mg (T2), 60 mg (T3), organic Cu : 12.5 mg (T4), 25 mg (T5), 37.5 mg (T6) andcombination of Cu + Zn: 12.5 mg + 20 mg (T7), 25 mg + 40 mg (T8), 37.5 mg + 60 mg (T9), respectively, per kg drymatter (DM) or fed without additional mineral supplementation (Control). Blood samples collected on days 120 and240 of treatment for analysis oftotal protein; albumin; cholesterol; high density lipoprotein (HDL) and glucose as wellas enzyme activities like Catalase (CAT), Superoxide dismutase (SOD), Glutathione reductase (GR) and Glutathioneperoxidase (GPx) were analyzed and correlated with spermatozoa functional characteristics. Significantly increased(P
Keywords: Zn; Cu; Goat; Blood plasma; Antioxidant enzymes; Sperm functional attributes